2019
DOI: 10.3390/nu11020240
|View full text |Cite
|
Sign up to set email alerts
|

Vegetable Nitrate Intakes Are Associated with Reduced Self-Reported Cardiovascular-Related Complications within a Representative Sample of Middle-Aged Australian Women, Prospectively Followed up for 15 Years

Abstract: Nitric oxide (NO) facilitates anti-atherosclerotic effects. Vegetables are a major source of dietary nitrate. Experimental data indicates that dietary nitrate can significantly reduce major risk factors for atherosclerosis and subsequent cardiovascular disease (CVD), as nitrate can be metabolized to produce NO via the nitrate-nitrite-NO pathway. The purpose of this study was to prospectively investigate the association between habitual dietary nitrate intakes and the incidence of self-reported CVD-related comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…A comprehensive database detailing the nitrate content of vegetables was used to calculate vegetable nitrate intake [3] in combination with a validated FFQ that included average intakes of foods commonly consumed in Denmark over the previous 12 months. The same up to date database was used in three previous smaller prospective studies [9][10][11][12], with results consistent with the current analysis. However, an older less comprehensive nitrate database was used in the Nurses Health Study [13].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…A comprehensive database detailing the nitrate content of vegetables was used to calculate vegetable nitrate intake [3] in combination with a validated FFQ that included average intakes of foods commonly consumed in Denmark over the previous 12 months. The same up to date database was used in three previous smaller prospective studies [9][10][11][12], with results consistent with the current analysis. However, an older less comprehensive nitrate database was used in the Nurses Health Study [13].…”
Section: Discussionsupporting
confidence: 82%
“…In participants of the Australian Blue Mountains Eye Study, those in the highest quartile of vegetable nitrate intake had a 27% lower risk of CVD mortality (188 incident cases) compared to those in the lowest intake quartile [ 12 ]. In women of Australian Longitudinal Study on Women’s Health, those in the highest quartile of vegetable nitrate intake had a 27% lower risk of developing self-reported CVD-related complications (1951 incident cases), compared to those in the lowest intake quartile [ 11 ]. In the American Nurses’ Health Study, women in the highest quintile of vegetable nitrate intake had weak evidence for a lower risk of either fatal or non-fatal CHD (2267 incident cases), compared to those in the lowest quintile [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, several plausible health benefits and preventive effects of nitrate have also been reported recently. A substantial number of studies in health and hypertensive subjects have now shown that nitrate has beneficial cardiovascular effects, including lowering of blood pressure [12][13][14][15][16][17] . Scientific evidence also suggests that having abundant vitamin C and polyphenol in fruits and vegetables facilitate in the nonenzymatic reduction of toxic nitrite to beneficial nitric oxide, thereby reducing the chances of nitrite reacting with secondary amines forming nitrosamines 18,19 .…”
Section: Study Of Nitrate Levels In Fruits and Vegetables To Assess Tmentioning
confidence: 99%
“…In addition, overfertilization of vegetables like lettuce, spinach, celery, and Chinese cabbage causes nitrate accumulation at levels of up to several g/kg fresh weight [44,45,46,47]. Possible health impacts of a high dietary intake of nitrate are intensively and controversially discussed [48,49,50,51,52,53,54,55].…”
Section: Introductionmentioning
confidence: 99%